Autobiographical Memory, Mental Disorders, and Emotional Valence: Comment on Young, et al. (2012). Issue 1 (August 2013) - Lemogne, Cédric; Limosin, Frédéric; Fossati, Philippe
Young, Erickson, and Drevets (2012) reported that positive and neutral cue words elicited less positive memories among patients with major depression than among healthy controls, while memories from patients were less specific than those from controls, regardless of their intrinsic valence. These results suggested methodological refinements that may shed light on several aspects of autobiographical memory impairment in mental disorders.